Preparation method of hexagonal crystal system BiPO4 catalyst and application of hexagonal crystal system BiPO4 catalyst in carbon dioxide electrocatalytic reduction

The preparation of the hexagonal BiPO4 catalyst by ion precipitation method solves the problems of competitive reaction inhibition and catalyst performance improvement of electrocatalytic reduction of carbon dioxide in the prior art, and achieves efficient, stable and highly selective formate production.

CN119774570APending Publication Date: 2025-04-08ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967864.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing carbon dioxide electrocatalytic reduction technologies face challenges of competitive reaction inhibition and improvement of catalyst performance, especially in improving selectivity and efficiency.

Method used

The hexagonal BiPO4 catalyst is prepared by ion precipitation method. This catalyst has rich oxygen content and high electron transfer rate, and is suitable for electrocatalytic reduction of carbon dioxide.

Benefits of technology

The hexagon BiPO4 catalyst significantly improves the selectivity and efficiency of carbon dioxide conversion to formate, has excellent electrocatalytic properties and good cycle durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774570A_ABST
    Figure CN119774570A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon dioxide reduction, and discloses a preparation method of a hexagonal crystal system BiPO4 catalyst and application of the hexagonal crystal system BiPO4 catalyst in carbon dioxide electrocatalytic reduction.The preparation method comprises the following steps that bismuth nitrate pentahydrate and polyvinylpyrrolidone are added into a mixed solvent of water and isopropanol, and a mixed solution is obtained; and adding diammonium hydrogen phosphate into the mixed solution, stirring for reaction, carrying out suction filtration, washing, collecting white precipitate, drying, and grinding to obtain the hexagonal crystal system BiPO4 catalyst. The hexagonal BiPO4 catalyst has higher electrochemical activity specific surface area, faster electrochemical reaction kinetics and high product selectivity and formate Faraday efficiency, and the catalyst is mild in preparation condition, simple to operate, good in repeatability, green and environment-friendly, and has the possibility of realizing large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide reduction, and more specifically relates to a preparation method of a hexagonal BiPO4 catalyst and its application in carbon dioxide electrocatalytic reduction. Background Art

[0002] With the acceleration of the global industrialization process, a large amount of fossil fuels are burned, resulting in a sharp increase in greenhouse gas emissions such as carbon dioxide (CO2), which in turn leads to global warming. In order to meet this challenge, countries have sought effective strategies to reduce greenhouse gas emissions. At the same time, energy supply shortage is also a major problem facing the world. The increasing depletion of traditional energy resources has made people urgently need to find new sustainable energy.

[0003] Reducing carbon dioxide to high-value-added chemical raw materials or fuels, such as single-carbon products such as methanol, methane, formic acid, and multi-carbon products such as ethanol and ethylene, is considered one of the effective strategies to overcome global warming and energy supply shortages. This conversion can not only achieve the reuse of carbon dioxide and reduce its accumulation in the atmosphere, but also help alleviate the energy crisis and promote sustainable development.

[0004] Compared with various technologies such as photocatalysis, photothermal catalysis and thermal catalysis, electrocatalytic carbon dioxide reduction (CO2RR) has the advantages of mildness, environmental friendliness and high energy conversion efficiency. Specifically: Mildness: Electrocatalytic reactions are usually carried out at room temperature and pressure, without high temperature and high pressure conditions, which reduces equipment costs and operational difficulties; Environmental friendliness: Fewer pollutants are generated during the electrocatalytic reaction, which helps protect the environment and ecological balance; High energy conversion efficiency: By optimizing electrode materials and catalytic systems, higher energy conversion efficiency can be achieved and resource utilization can be improved.

[0005] At present, research in the field of electrocatalytic reduction of carbon dioxide is still in its infancy and still faces many challenges, including competing reactions and catalyst design. Electrocatalytic reaction is a redox process carried out in aqueous solution. Hydrogen evolution reaction (HER) is the main competing reaction of CO2RR. How to effectively inhibit HER and improve the selectivity and efficiency of CO2RR is one of the current research focuses. Catalyst performance also has an important influence on the efficiency and product distribution of CO2RR. At present, although a variety of catalyst systems have been developed, there are still problems such as high cost, poor stability, and difficult to control product selectivity. Therefore, designing efficient, stable and selective catalysts is one of the future research directions. Summary of the invention

[0006] The main purpose of the present invention is to provide a method for preparing a hexagonal BiPO4 catalyst and its application in the electrocatalytic reduction of carbon dioxide in view of the above problems. Hexagonal BiPO4 is synthesized by ion precipitation method. This is a typical oxoacid salt with rich oxygen content, providing the possibility of having more residual oxygen to form active sites, low interface resistance, high electron transfer rate, and thus excellent electrocatalytic performance. The catalyst can improve the selectivity of the electrocatalytic reduction of carbon dioxide to formate, and has great potential in the practical application of electrocatalytic carbon dioxide reduction.

[0007] Bismuth nitrate pentahydrate will dissolve in water, providing the bismuth source in BiPO4. Polyvinylpyrrolidone is used as a growth indicator to make it grow linearly. Isopropyl alcohol is used as a dispersant to refine the grains. After diammonium hydrogen phosphate is added as the phosphorus source in BiPO4, a suspension will be immediately produced to generate BiPO4 precipitation. Among them, nitrate and ammonium salt can be dissolved in water and can be removed with the filtrate during the filtration process. Drying at low temperature makes it easier to decompose the residual nitrate ions and ammonium ions to obtain purified hexagonal BiPO4.

[0008] The present invention obtains a hexagonal BiPO4 catalyst by a simple ion precipitation method, has mild reaction conditions, simple operation steps, and is suitable for mass production. The catalyst of the present invention has a fast charge transfer rate, and is applied to electrocatalytic carbon dioxide reduction, and has excellent electrocatalytic carbon dioxide reduction performance and good cycle durability.

[0009] The reaction pathway for the conversion of carbon dioxide to formate is as follows:

[0010] O=C=O+H + +e - → * O-CH-O *

[0011] * O-CH-O*+H + +e - →O=CH-OH

[0012] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0013] One of the technical solutions of the present invention: a method for preparing a hexagonal BiPO4 catalyst, comprising the following steps: adding bismuth nitrate pentahydrate and polyvinyl pyrrolidone to a mixed solvent of water and isopropanol to obtain a mixed solution; adding diamine hydrogen phosphate to the mixed solution, stirring for reaction, filtering, washing, collecting a white precipitate, drying, and grinding to obtain a hexagonal BiPO4 catalyst.

[0014] Further preferably, the added amounts of bismuth nitrate pentahydrate and diammonium hydrogen phosphate are such that the molar ratio of bismuth to phosphorus is 1:1.

[0015] Further preferably, the ratio of the added amount of bismuth nitrate pentahydrate and polyvinylpyrrolidone is 5mM:0.6-0.8g.

[0016] Further preferably, the average molecular weight of the polyvinyl pyrrolidone is 1,000,000-1,500,000 g / mol.

[0017] Further preferably, the volume ratio of water to isopropanol is 3:2-4.

[0018] Further preferably, the ratio of the added amount of bismuth nitrate pentahydrate and isopropanol is 5mM:20-40mL.

[0019] More preferably, the stirring time is 4-6 hours.

[0020] More preferably, the drying temperature is 120° C.-140° C., and the drying time is 10-12 h.

[0021] The second technical solution of the present invention: application of a hexagonal BiPO4 catalyst in the electrocatalytic reduction of carbon dioxide.

[0022] Further preferably, a hexagonal BiPO4 catalyst is used to prepare a working electrode, a CO2-saturated KHCO3 solution is used as an electrolyte, and an electrocatalytic reduction reaction is carried out in an H-type electrolytic cell.

[0023] The liquid product is formate, and the gaseous product is a small amount of carbon monoxide and hydrogen.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) The hexagonal BiPO4 catalyst of the present invention has a large reaction specific surface area due to the reconstructed nanoflower structure and mesh structure, exposing more active sites, so it has higher conductivity and a higher current density at -1.2V vs. RHE, which can reach 80mA·cm -2 , it can reach 40mA·cm at -1V vs.RHE -2 of current density.

[0026] (2) The hexagonal BiPO4 catalyst of the present invention has high product selectivity. In its hydrogen nuclear magnetic resonance spectrum, in addition to the peak of H2O and the peak of internal standard deuterated dimethyl sulfoxide (DMSO), only formate (HCOO - ) peak, and no other impurity peaks.

[0027] (3) The hexagonal BiPO4 catalyst of the present invention has a high formate Faraday efficiency, and has a formate Faraday efficiency of 90% at a wide potential range of -1.53 ​​V to 1.83 V vs. RHE.

[0028] (4) The hexagonal BiPO4 catalyst of the present invention has a higher electrochemically active specific surface area and faster electrochemical reaction kinetics.

[0029] (5) The hexagonal BiPO4 catalyst prepared by the present invention adopts non-precious metal element compound raw materials, which are low in price and abundant in resources, thereby reducing the preparation cost of the catalyst; the preparation method of the catalyst has mild experimental conditions, simple operation, good repeatability, and is green and environmentally friendly, and has the possibility of realizing large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the XRD diffraction pattern of the synthesized hexagonal BiPO4 catalyst (HG-BiPO4);

[0031] Figure 2 XRD diffraction patterns of Bi2O3 in Comparative Example 1 and monoclinic BiPO4 catalyst (MG-BiPO4) in Comparative Example 2;

[0032] Figure 3 The electrochemical polarization curves (LSV) of the hexagonal BiPO4 catalyst (HG-BiPO4) in Example 1, the Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst (MG-BiPO4) in Comparative Example 2;

[0033] Figure 4 CV curves and double layer capacitance (Cdl) curves of the hexagonal BiPO4 catalyst (HG-BiPO4) in Example 1, Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst (MG-BiPO4) in Comparative Example 2.

[0034] Figure 5 The Tafel slope is obtained based on the electrochemical polarization curve data of the hexagonal BiPO4 catalyst (HG-BiPO4) in Example 1, the Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst (MG-BiPO4) in Comparative Example 2;

[0035] Figure 6 The hydrogen nuclear magnetic resonance spectrum of the electrolyte obtained after the hexagonal BiPO4 catalyst in Example 1 was reacted in a CO2-saturated 0.5M KHCO3 solution at -0.9V vs. RHE for 6 hours;

[0036] Figure 7is the Faraday efficiency of the product of the hexagonal BiPO4 catalyst in Example 1 at different voltages in a 0.5M KHCO3 solution saturated with CO2;

[0037] Figure 8 The catalyst stability test (-0.9 V vs. RHE) of the hexagonal BiPO4 catalyst in Example 1 was carried out in a 0.5 M KHCO3 solution saturated with CO2;

[0038] Fig. 9 The SEM image and mapping image of the hexagonal BiPO4 catalyst before the reaction in Example 1;

[0039] Fig.10 The TEM image and mapping image of the hexagonal BiPO4 catalyst before the reaction in Example 1;

[0040] Fig.11 The SEM image and mapping image of the hexagonal BiPO4 catalyst in Example 1 after reacting for 180 min in a 0.5M KHCO3 solution saturated with CO2, and the mapping image corresponds to a mesh shape and a flower shape, respectively;

[0041] Fig.12 The XRD diffraction pattern of the hexagonal BiPO4 catalyst in Example 1 after reacting for 180 min in a 0.5M KHCO3 solution saturated with CO2;

[0042] Fig.13 The SEM image and mapping image of the monoclinic BiPO4 catalyst before the reaction in Comparative Example 2;

[0043] Fig.14 The SEM image and mapping image of the monoclinic BiPO4 catalyst in Comparative Example 2 reacted for 180 min in a CO2-saturated 0.5M KHCO3 solution. DETAILED DESCRIPTION

[0044] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0045] Comparative Example 1: Preparation of Bi2O3 Catalyst

[0046] (1) Dissolve 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) in a mixed solvent of 30 mL deionized water and 20 mL isopropanol and stir for 10 min.

[0047] (2) The mixed solution obtained in (1) was placed in a 100 mL reactor, heated to 120° C. in an oven, and the reaction was continued for 12 h. After the reactor was naturally cooled to room temperature, the solid product in the reactor was collected.

[0048] (3) The solid product obtained in (2) was placed in a quartz boat, and the temperature was raised to 500°C at a heating rate of 5°C / min in a tube furnace under air atmosphere, and kept at this temperature for 2 h. After natural cooling, the product was collected, which was a Bi2O3 catalyst.

[0049] (4) Take 5 mg of Bi2O3 catalyst and put it into a 2 mL centrifuge tube, add 50 μL of Nafion solution and 950 μL of ethanol, and sonicate on an ultrasonic machine for 1 h to obtain catalyst ink.

[0050] (5) 100 μL of the catalyst ink was dropped onto a 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a Bi2O3 catalyst working electrode.

[0051] Comparative Example 2: Preparation of monoclinic BiPO4 catalyst

[0052] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 20 mL isopropanol, and 20 mM diammonium hydrogen phosphate was added, and stirring was continued for 10 min.

[0053] (2) The mixed solution obtained in (1) was placed in a 100 mL reactor, heated to 120° C. in an oven, and the reaction was continued for 12 h. After the reactor was naturally cooled to room temperature, the solid product in the reactor was collected.

[0054] (3) The solid product obtained in (2) is placed in a quartz boat, and heated to 500°C at a heating rate of 5°C / min in a tube furnace under air atmosphere, and kept at this temperature for 2 hours. The crystals calcined at high temperature will undergo recrystallization and phase transformation from a low-temperature hexagonal phase to a high-temperature monoclinic phase. After natural cooling, the product is collected, which is a monoclinic BiPO4 catalyst.

[0055] (4) 5 mg of monoclinic BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0056] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a monoclinic BiPO4 catalyst working electrode.

[0057] Example 1: Preparation of hexagonal BiPO4 catalyst

[0058] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 20 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 4 h.

[0059] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0060] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 12 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0061] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0062] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0063] Example 2: Preparation of Hexagonal BiPO4 Catalyst

[0064] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 30 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 4 h.

[0065] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0066] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 12 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0067] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0068] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0069] Example 3: Preparation of hexagonal BiPO4 catalyst

[0070] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 40 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 4 h.

[0071] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0072] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 12 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0073] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0074] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0075] Example 4: Preparation of Hexagonal BiPO4 Catalyst

[0076] (1) 5 mM bismuth nitrate pentahydrate and 0.8 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 20 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 4 h.

[0077] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0078] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 12 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0079] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0080] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0081] Example 5: Preparation of Hexagonal BiPO4 Catalyst

[0082] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 20 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 6 h.

[0083] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0084] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 12 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0085] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0086] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0087] Example 6: Preparation of Hexagonal BiPO4 Catalyst

[0088] (1) 5 mM bismuth nitrate pentahydrate and 0.6 g polyvinyl pyrrolidone (average molecular weight 1300000 g / mol) were dissolved in a mixed solvent of 30 mL deionized water and 20 mL isopropanol, and 5 mM diammonium hydrogen phosphate was added, and stirring was continued for 4 h.

[0089] (2) The mixed solution obtained in (1) was filtered with a suction filter, and the collected precipitate was washed three times with deionized water and ethanol in sequence.

[0090] (3) The solid precipitate obtained in (2) was placed in an oven at 120° C. and dried for 10 h. The solid product was collected by grinding, which was a hexagonal BiPO 4 catalyst.

[0091] (4) 5 mg of hexagonal BiPO4 catalyst was placed in a 2 mL centrifuge tube, 50 μL of Nafion solution and 950 μL of ethanol were added, and the mixture was sonicated for 1 h on an ultrasonic machine to obtain catalyst ink.

[0092] (5) 100 μL of catalyst ink was dropped onto 1*2 cm carbon paper and dried in an oven at 60°C for 0.5 h to obtain a hexagonal BiPO4 catalyst working electrode.

[0093] Performance Test:

[0094] like Figure 1Shown is the X-ray diffraction pattern of the prepared hexagonal BiPO4 catalyst, which is completely consistent with the diffraction peak position of the standard card PDF#15-0766 in the database, indicating that the catalyst was successfully prepared and there are no diffraction peaks of other irrelevant impurities, indicating that the synthesized catalyst has high purity.

[0095] like Figure 2 Shown are the X-ray diffraction patterns of the hexagonal BiPO4 catalyst prepared in Example 1 and the catalysts in Comparative Examples 1 and 2. Figure 2 It can also be seen that the catalyst was successfully synthesized and all of them are pure phases.

[0096] like Figure 3 The electrochemical polarization curves (LSV) of the hexagonal BiPO4 catalyst prepared in Example 1, the Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst in Comparative Example 2 in an H-type electrolyzer in a CO2-saturated 0.5M KHCO3 solution are shown. Figure 3 It can be observed that the hexagonal BiPO4 catalyst can show a sharp increase in current at a lower potential, indicating that the hexagonal BiPO4 catalyst has a higher CO2RR catalytic activity than the other two. At a voltage of -1.1 V vs. RHE, the current density of the hexagonal BiPO4 catalyst can reach 46 mA cm -2 .

[0097] like Figure 4 Shown are CV curves of the hexagonal BiPO4 catalyst in Example 1, the Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst in Comparative Example 2 measured by the CV cycle method at different scan rates in a CO2-saturated 0.5M KHCO3 solution, thereby obtaining double layer capacitance (Cdl) curves. It can be seen from the figure that the hexagonal BiPO4 catalyst has a larger Cdl value, which also shows from the side that its electrochemically active specific surface area is larger.

[0098] like Figure 5 The figure shows the Tafel slopes obtained from the electrochemical polarization curve data of the hexagonal BiPO4 catalyst in Example 1, the Bi2O3 in Comparative Example 1, and the monoclinic BiPO4 catalyst in Comparative Example 2 in a CO2-saturated 0.5M KHCO3 solution. The hexagonal BiPO4 catalyst has a lower value, indicating a faster electron transfer rate in the solution and an easier reaction.

[0099] like Figure 6 The figure shows the hydrogen nuclear magnetic resonance spectrum of the electrolyte of the hexagonal BiPO4 catalyst in Example 1 after reacting in a CO2-saturated 0.5M KHCO3 solution at -0.9V vs. RHE for 6 hours. The peaks in the spectrum reveal the uniqueness of the liquid product, which is formate.

[0100] like Figure 7 The figure shows the Faraday efficiency of the product of the hexagonal BiPO4 catalyst of Example 1 at different voltages in a CO2-saturated 0.5M KHCO3 solution. It can be seen from the figure that it has a high FEFormate of about 90% at a wide potential of -1.53 ​​to -1.83 V vs. RHE.

[0101] like Figure 8 The figure shows the catalyst stability test (-0.9 V vs. RHE) of the hexagonal BiPO4 catalyst in Example 1 in a 0.5 M KHCO3 solution saturated with CO2. The catalyst can react at a potential of -12 mA·cm at a potential of -0.9 V vs. RHE. -2 The current density was kept stable for 24h.

[0102] like Fig. 9 The SEM image and mapping image of the hexagonal BiPO4 catalyst of Example 1 before the reaction are shown. The structure of the catalyst before the reaction is a compactly stacked nanorod shape, in which Bi, P, and O elements are evenly distributed.

[0103] like Fig.10 The TEM image, electron diffraction image and mapping image of the hexagonal BiPO4 catalyst of Example 1 are shown. The catalyst is a nanorod-like structure in which Bi, P and O elements are evenly distributed. The electron diffraction image proves that it is a single crystal.

[0104] like Fig.11 Shown are the SEM image and mapping image of the hexagonal BiPO4 catalyst in Example 1 after reacting in a CO2-saturated 0.5M KHCO3 solution for 180 minutes. Due to the electrochemical reconstruction, the structure of the catalyst is transformed from compactly stacked nanorods to a loose and porous nanoflower network structure, which increases the specific surface area of ​​the catalyst, thereby increasing more catalytic active sites and making it easier to convert CO2 into formate.

[0105] like Fig.12 Shown is the XRD diffraction pattern of the hexagonal BiPO4 catalyst of Example 1 reacted in a CO2-saturated 0.5M KHCO3 solution for 180 min. The catalyst was reduced at the cathode, resulting in electrochemical reconstruction. The reconstructed substances were two phases of Bi (PDF#44-1246) and Bi2O2CO3 (PDF#04-0666).

[0106] like Fig.13 Shown are the SEM image and mapping image of the monoclinic BiPO4 catalyst of comparative example 2 before the reaction. The structure of the catalyst before the reaction is compactly stacked nanoparticles, in which Bi, P, and O elements are evenly distributed.

[0107] like Fig.14 Shown are the SEM image and mapping image of the monoclinic BiPO4 catalyst in comparative example 2 after reacting in a CO2-saturated 0.5M KHCO3 solution for 180 minutes. The catalyst is transformed from compactly stacked nanoparticles into a sparse nanoflower sheet structure. Compared with the hexagonal BiPO4 catalyst in Example 1, the catalyst has a smaller specific surface area and fewer catalytic active sites, and thus has a lower catalytic efficiency.

[0108] Table 1

[0109] catalyst Current density <![CDATA[FE formate ]]> Comparative Example 1 <![CDATA[-18.42mA·cm -2 ]]> 74.17% Comparative Example 2 <![CDATA[-30.17mA·cm -2 ]]> 84.26% Example 1 <![CDATA[-46.52mA·cm -2 ]]> 92.22% Example 2 <![CDATA[-46.37mA·cm -2 ]]> 91.14% Example 3 <![CDATA[-46.08mA·cm -2 ]]> 91.38% Example 4 <![CDATA[-46.19mA·cm -2 ]]> 90.82% Example 5 <![CDATA[-45.93mA·cm -2 ]]> 92.54% Example 6 <![CDATA[-45.82mA·cm -2 ]]> 91.69%

[0110] As shown in Table 1, the current density comparison of Comparative Examples 1-2 and Examples 1-6 at -1.1V vs. RHE in a CO2-saturated 0.5M KHCO3 solution and the Faraday efficiency of formate production at this potential are shown. It can be seen from the table that the electrochemical performance and Faraday efficiency of Examples 1-6 are better than those of Comparative Examples 1-2, and the current density is -46mA·cm -2 Above, the formate Faraday efficiency is above 90%.

[0111] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a hexagonal BiPO4 catalyst, characterized in that: The method comprises the following steps: adding bismuth nitrate pentahydrate and polyvinyl pyrrolidone into a mixed solvent of water and isopropanol to obtain a mixed solution; adding diammonium hydrogen phosphate into the mixed solution, stirring for reaction, filtering, washing, collecting white precipitates, drying and grinding to obtain a hexagonal BiPO4 catalyst.

2. The method for preparing the hexagonal BiPO4 catalyst according to claim 1, characterized in that: The added amounts of the bismuth nitrate pentahydrate and diammonium hydrogen phosphate are such that the molar ratio of bismuth to phosphorus is 1:

1.

3. The method for preparing the hexagonal BiPO4 catalyst according to claim 1, characterized in that: The ratio of the added amounts of bismuth nitrate pentahydrate and polyvinylpyrrolidone is 5mM:0.6-0.8g.

4. The method for preparing a hexagonal BiPO4 catalyst as claimed in any one of claims 1 to 3, characterized in that: The average molecular weight of the polyvinyl pyrrolidone is 1,000,000-1,500,000 g / mol.

5. The method for preparing the hexagonal BiPO4 catalyst according to claim 1, characterized in that: The volume ratio of the water to the isopropanol is 3:2-4.

6. The method for preparing a hexagonal BiPO4 catalyst as claimed in claim 1 or 5, characterized in that: The ratio of the added amounts of bismuth nitrate pentahydrate and isopropanol is 5mM:20-40mL.

7. The method for preparing the hexagonal BiPO4 catalyst according to claim 1, characterized in that: The stirring time is 4-6h.

8. The method for preparing a hexagonal BiPO4 catalyst as claimed in claim 1 or 7, characterized in that: The drying temperature is 120° C.-140° C., and the drying time is 10-12 hours.

9. Use of a hexagonal BiPO4 catalyst prepared by the preparation method according to any one of claims 1 to 8 in the electrocatalytic reduction of carbon dioxide.

10. The use of the hexagonal BiPO4 catalyst in the electrocatalytic reduction of carbon dioxide as claimed in claim 9, characterized in that: The working electrode was prepared by using hexagonal BiPO4 catalyst, and the electrocatalytic reduction reaction was carried out in an H-type electrolytic cell by using CO2-saturated KHCO3 solution as electrolyte.